Intrauterine Malnutrition Reduced Long Leptin Receptor Isoform Expression and Proinflammatory Cytokine Production in Male Rat Pulmonary Endothelial Cells Stimulated by Lipopolysaccharide - Aleksandro M. Balbino; Marina M. Silva; Gabriela A. Azevedo; Noemi L. Gil; Renaide R. Ferreira; Leila A. dos Santos; Rebéca M. Gasparin; Liliam Fernandes; Maristella A. Landgraf; Richardt G. Landgraf (Hindawi Limited, 2018)
Background/Aims. We have previously shown that low birth weight (LBW) rats exposed to intrauterine malnutrition have an impaired lung inflammatory response and reduced levels of inflammatory mediators; however, circulating leptin levels were not increased. We evaluated long leptin receptor isoform (ObRb) expression in lung endothelial cells from low birth weight rats and examined its role in the production of lipid mediators and cytokines. Methods. Lung endothelial cells were obtained from normal birth weight (NBW) rats or LBW rats subjected to intrauterine malnutrition. These cells were stimulated with leptin (10 ng/mL), LPS (lipopolysaccharide, 1 μg/mL), or leptin plus LPS. Six hours after stimulation, the production of inflammatory mediators (PGE2, LTB4, IL-1β, and IL-6) was evaluated using commercial ELISA kits, and Western blotting was performed to investigate p38MAPK, NF-κB, and ObRb expression. Results. Leptin increased IL-1β levels in only cells from the NBW group, whereas LPS increased PGE2 and LTB4 levels in cells from both groups; leptin addition potentiated lipid mediator production induced by LPS in the NBW group. LPS enhanced the production of IL-1β and IL-6 in only endothelial cells from NBW rats. Leptin receptor expression was decreased (63%) in endothelial cells from LBW rats. None of the stimuli increased NF-κB or p38 signaling pathway expression in cells from LBW rats. Conclusion. These results suggest that intrauterine malnutrition compromises leptin receptor expression and cytokine production in pulmonary endothelial cells stimulated by LPS; these effects seem to involve the NF-κB and p38MAPK signaling pathways.